Exploring the factors involved in being "ready" to return to sport following a concussion - Caron, J. G.; Cadotte, G.; Collict, C.; van Ierssel, J. J.; Podlog, L. (Clinical Journal of Sport Medicine, 2023)
Objective: To explore the factors involved in athletes being ready (or not) to return to sport (RTS) after sport-related concussion (SRC).